2011
DOI: 10.1111/j.1439-037x.2010.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Drought Tolerance in Maize (Zea mays L.) due to Exogenous Application of Trehalose: Growth, Photosynthesis, Water Relations and Oxidative Defence Mechanism

Abstract: The present investigation was conducted to assess the ameliorative effects of foliar‐applied trehalose on growth, photosynthetic attributes, water relation parameters and oxidative defence mechanism in two maize cultivars under field water deficit conditions. Various components of the experiment comprised two maize cultivars (EV‐1098 and Agaiti‐2002), two water‐stress levels (irrigation after 2 weeks and irrigation after 3 weeks during the entire period of growth), and two levels of trehalose (0 and 30 mm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
150
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 62 publications
26
150
3
2
Order By: Relevance
“…In addition they observed that decrease of t-ferulic acid was around 35 and 31% after drought treatment in the studied hybrids which is in the range of the present study. Ali and Ashraf (2011) studied the effect of drought treatment on the secondary metabolites of maize leaves and they found decreasing levels around 27 and 25% in total phenols for ʽEV-1098ʼ and ʽAgaiti-2002ʼ maize cultivars, being these results lower than the current data. Alvarez et al (2008) analysed xylem sap of ʽFR697ʼ maize cultivar after 12 days of drought treatment and they observed the same pattern of hydroxycinnamic acids composition of the present study, reporting that t-ferulic acid was the predominant with a decreasing of 46% of this compound after drought treatment and this result was higher than the current experiment, in addition p-coumaric acid increased 286% which is a different behaviour comparing with the current results.…”
Section: Total Phenols and Hydroxycinnamic Acidscontrasting
confidence: 69%
“…In addition they observed that decrease of t-ferulic acid was around 35 and 31% after drought treatment in the studied hybrids which is in the range of the present study. Ali and Ashraf (2011) studied the effect of drought treatment on the secondary metabolites of maize leaves and they found decreasing levels around 27 and 25% in total phenols for ʽEV-1098ʼ and ʽAgaiti-2002ʼ maize cultivars, being these results lower than the current data. Alvarez et al (2008) analysed xylem sap of ʽFR697ʼ maize cultivar after 12 days of drought treatment and they observed the same pattern of hydroxycinnamic acids composition of the present study, reporting that t-ferulic acid was the predominant with a decreasing of 46% of this compound after drought treatment and this result was higher than the current experiment, in addition p-coumaric acid increased 286% which is a different behaviour comparing with the current results.…”
Section: Total Phenols and Hydroxycinnamic Acidscontrasting
confidence: 69%
“…Ali and Ashraf (2011) mentioned that trehalose is an efficient protectant against water deficit conditions. Exogenous trehalose application was also effective in reducing oxidative stress (Ma et al, 2013).…”
Section: Role Of Trehalose In Mitigating Water Stressmentioning
confidence: 99%
“…These defense mechanisms are employed to overcome the stress and restore normal metabolism (Soares;Machado, 2007, Ali;Ashraf, 2011;Karuppanapandian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%